Late Holocene Subsistence Practices Among Cis-Baikal Pastoralists, Siberia: Zooarchaeological Insights from Sagan-Zaba II - NOMOKONOVA, TATIANA; LOSEY, ROBERT J.; WEBER, ANDRZEJ; GORIUNOVA, OL'GA I.; NOVIKOV, ALEKSEI G. (Asian perspectives (Honolulu), 2010)
Roughly 3000 years ago, nomadic pastoralists began to arrive in the Cis-Baikal region of eastern Siberia. While the archaeological record of these groups is quite extensive, most research on pastoralists here has focused on mortuary traditions while questions about subsistence practices have been left largely unaddressed. Few habitation sites from the late Holocene here contain stratified deposits, and virtually none have been subject to modern excavation methods or zooarchaeological analyses. We present new faunal data from the recently excavated Sagan-Zaba II site located on the west coast of Lake Baikal. This site offers a unique opportunity to examine diachronic patterns in diet and subsistence practices of local pastoralists. It contains stratified deposits associated with different periods of pastoralist occupation spanning much of the late Holocene. Significantly, it is the first site of this period in the region to be screened with fine-meshed sieves and to be systematically studied by zooarchaeologists. The results of our research reveal a series of new insights on pastoralist subsistence practices. First, the primary domesticates in all periods were sheep, goats, cattle, and horses. Cattle appear to increase through time at the site while horses remained relatively rare. Second, pastoralists at Sagan-Zaba regularly hunted Lake Baikal's freshwater seals, long after the introduction of domesticated livestock. Third, hunting of terrestrial mammals, particularly roe deer and red deer, was also common at the site. Finally, our data demonstrate that pastoralists here also regularly fished. This subsistence practice was previously unrecognized in the region, likely due to lack of sieving of sites. Furthermore, these data suggest that historically documented fishing by modern local pastoralists and increases in sedentism were not completely the result of Russian-period settlement of the region but instead were occurring in Cis-Baikal long prior to the modern era.